Bodenzoologie der amazonischen Uberschwemmungswalder - Beck, Ludwig (Amazoniana, 1983)
The present paper, originally presented orally, desribes research initiated by SCHALLER on the soil fauna of Amazonian inundation forests, including ecophysiological questions concerning the spatial distribution of particular species of land-water boundaries. BECK and IRMLER dealt mainly with the population dynamics of inundation forest species and their adaptation to the particular conditions of the environment, especially in relation to the survival of terrestrial organisms during periods of inundation. Movement on the ground.to avoid rising water levels, as weli as movement up tree trunks to the canopy (ADIS) plays an important role, although nevertheless much of the smali soil fauna is inundated.
Soil zoology in the inundation forests of Amazonia
Keywords: Florestas Inundáveis